Can new-type urbanization improve the green total factor energy efficiency? Evidence from China - Shao, Jun; Wang, Lianghu (Energy (Oxford), 2023)
As an important driving force of high-quality urban development, developing new-type urbanization plays an irreplaceable role in realizing urban sustainable development goals. The existing work has conducted extensive research on the impact of new-type urbanization. However, the underlying mechanism and empirical evidence of its impact on green total factor energy efficiency (GTFEE) have not been systematically studied. Therefore, based on the panel data at the prefecture-level city level, this paper uses a dynamic panel data model to empirically verify the impact of developing new-type urbanization on GTFEE. The current work demonstrates the following results. First, developing new-type urbanization shows a fluctuating growth trend, and it has significantly promoted GTFEE improvement. Second, considering the factors of urban heterogeneity, the results reveal that new-type urbanization has a heterogeneous impact on GTFEE of different cities. Furthermore, the analysis of impact mechanism indicates that the effects of industrial structure and technological innovation are crucial channels for new-type urbanization to affect GTFEE. The new-type urbanization can also positively regulate its relationship with GTFEE by interacting with industrial structure upgrading and technological innovation. •The new-type urbanization shows a trend of fluctuating growth.•The new-type urbanization has significantly promoted GTFEE improvement.•The effects of industrial structure and technological innovation are crucial channels.